An Assay for Screening Potential Drug Candidates for Alzheimer's Disease That Act as Chaperones of the Transthyretin and Amyloid‐β Peptides Interaction. Issue 72 (19th November 2020) - Cotrina, Ellen Y.; Gimeno, Ana; Llop, Jordi; Jiménez‐Barbero, Jesús; Quintana, Jordi; Prohens, Rafel; Cardoso, Isabel; Arsequell, Gemma
Abstract: The protein transthyretin (TTR) modulates amyloid‐β (Aβ) peptides deposition and processing and this physiological effect is further enhanced by treatment with iododiflunisal (IDIF), a small‐molecule compound (SMC) with TTR tetramer stabilization properties, which behaves as chaperone of the complex. This knowledge has prompted us to design and optimize a rapid and simple high‐throughput assay that relies on the ability of test compounds to form ternary soluble complexes TTR/Aβ/SMC that prevent Aβ aggregation. The method uses the shorter Aβ(12–28) sequence which is cheaper and simpler to use while retaining the aggregation properties of their parents Aβ(1–40) and Aβ(1–42). The test is carried out in 96‐plate wells that are UV monitored for turbidity during 6 h. Given its reproducibility, we propose that this test can be a powerful tool for efficient screening of SMCs that act as chaperones of the TTR/Aβ interaction that may led to potential AD therapies. Abstract : Potential drug candidates for Alzheimer's disease: A simple high throughput screening assay for chaperones of the transthyretin and amyloid‐β peptides interaction.